Women and peacebuilding in Guinea-Bissau - Carvalho, C. (2020)
Women’s organisations aimed at conflict resolution have been active in Guinea-Bissau in the past decade under the auspices of international and regional bodies, particularly the Economic Community of West African States (ECOWAS) and the United Nations (UN). Guinea-Bissau is a small Western African country of 1.8 million habitants that declared its independence from Portugal in 1973 after a long independent war. The country recent history has been marked by repeated military coups, political assassinations, and the fragility of state institutions. In this article we ask what was the role of women organisations in peacebuilding and conflict resolution in a country marked by a prolonged and systemic political crisis?